Synthesis of current research on the affective dimensions of online English language education: Theories and praxis - Chiew Hong Ng; Yin Ling Cheung (Australian Journal of Applied Linguistics)
The affective domain can impact the way teachers teach and students’ motivation and engagement in learning in online contexts. This study focuses on the affective dimensions of online English language education by offering a comprehensive overview of the diverse types of emotions experienced by both students and teachers in online English language environments in terms of (1) the types of emotions and participants studied in specific virtual environments, (2) the theoretical approaches and pedagogical practices for studying emotions in online English language education, and (3) the methodological design features of the studies. Thematic analysis of the 40 selected studies highlighted these feelings as the focus, namely boredom, emotion regulation, emotional labour, emotional intelligence, stress, emotions towards L2 learning, foreign language enjoyment (FLE), FLE and foreign language anxiety/foreign language classroom anxiety, foreign language speaking anxiety, and positive and achievement emotions. The findings revealed the use of established theoretical frameworks such as control-value theory, the emotion regulation scale, the FLE and foreign language anxiety scales and other instruments, as well as questionnaires, interviews and multiple instruments to study emotions in online English language education. Educators can consider the emotionally resilient pedagogical practices identified in this study such as emotional scaffolding strategies and technologyassisted language learning or mobile-based language learning for emotion regulation in teaching and learning English online.